The Hunnu’s land relations: A characteristic of Mongolian thoughts /Xiongnu/ (Mongolian Journal of Arts and Culture, 2024)
The Hunnu Empire is the first–ever statehood established in the territory of Mongolia, and the period of establishment of the Hunnu Empire is the historical period when the ancient nomads in Central Asia united all of their civilization under the flag of one nation. Although, according to explanations in the history and theory of the state, the Mongolians derived the path to statehood from the Hunnu Empire, in fact, we derived independent state-culture-civilization from the Hunnu Empire through the statehood tradition. The national origin, culture, social structure, state structure, and system, as well as the economy, are the comprehensive structure to be considered as a whole and complex, and the fundamental principle was based on legislation and old customs promoted by the law of nature. These legislation and old customs were realized through the military–administrative system broadly spread in the Hunnu society, and this principle has been developed to the highest-order thougths through the “spiritual order”. This is the fundamental essence of thougths for today’s Mongolians. Accordingly, we can say that the Huns are the ancestors of modern Mongolians as per the tradition of the fundamental essence of national thoughts.Хүннүгийн газрын харилцааны онцлог чанар нь монголчуудын сэтгэлгээний үндэс болох тухайдХураангуй: Хүннү нь монгол газар нутагт байгуулагдсан анхны төрт улс агаад Хүннү гүрэн байгуулагдсан нь төв ази дахь тал нутгийн эртний нүүдэлчдийн соёл иргэншлийг нэг үндэстний тугийн дор нэгтгэсэн түүхэн мөчлөг үе юм. Монголчууд Хүннү гүрнээс төрийн улбааг авсан хэмээн төрийн түүх, онол талаас харж буй ч бид хүннүгээс төрт ёсны уламжлалаар дамжуулаад бүхэл бүтэн нүүдлийн бие даасан төр-соёл-иргэншлийг нь уламжилж авсан билээ. Хүннү гүрний угсаа, соёл, нийгмийн бүтэц, төрийн удирдлагын бүтэц тогтолцоо, аж ахуй зэрэг нь цогцоор авч үзэх шаардлагатай цогц байгууламж бөгөөд гол зарчим нь байгалийн жамд нийцсэн “ёс”-нд тулгуурласан зарчимтай байв. Уг ёс нь нийт хүннүгийн нийгмийг бүрхсэн цэрэг-захиргааны тогтолцоогоор дамжиж хэрэгждэг байсан бөгөөд эл зарчим нь “тэнгэрийн ёс”-ны ойлголтоор дамжин сэтгэлгээний хийсвэр дээд түвшинд хүртлээ хөгжсөн нь өнөөгийн монголчуудын сэтгэлгээний язгуур чанар билээ. Тиймд угсаатны сэтгэлгээний язгуур чанарын уламжлалаар бол Хүннү гүрэн нь өнөөгийн монголчуудын шууд өвөг мөн юм. Түлхүүр үгс: газар нутаг, ёс, ёс заншил, төрт ёс, тэнгэрчлэл